2007
DOI: 10.1095/biolreprod.107.061705
|View full text |Cite
|
Sign up to set email alerts
|

Negative Effect of Estradiol on Luteinizing Hormone Throughout the Ovulatory Luteinizing Hormone Surge in Mares1

Abstract: The negative effect of estradiol-17beta (E2) on LH, based on exogenous E2 treatments, and the reciprocal effect of LH on endogenous E2, based on hCG treatments, were studied throughout the ovulatory follicular wave during a total of 103 equine estrous cycles in seven experiments. An initial study developed E2 treatment protocols that approximated physiologic E2 concentrations during the estrous cycle. On Day 13 (ovulation = Day 0), when basal concentrations of E2 and LH precede the ovulatory surges, exogenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 36 publications
3
10
0
1
Order By: Relevance
“…35 and present data, Fig.5), consistent with the proposed role for estradiol in the positive feed-back leading to ovulation [25,30,33]. Nevertheless, in contrast to ovine or cattle for instance, the very existence of a positive feed-back effect of estradiol at any point of the periovulatory LH surge in mare remains controversial (refs [35][36][37], see below). The long-lasting LH increase in mare appears mandatory to induce maturation of dominant-size follicles leading to ovulatory competence [38].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…35 and present data, Fig.5), consistent with the proposed role for estradiol in the positive feed-back leading to ovulation [25,30,33]. Nevertheless, in contrast to ovine or cattle for instance, the very existence of a positive feed-back effect of estradiol at any point of the periovulatory LH surge in mare remains controversial (refs [35][36][37], see below). The long-lasting LH increase in mare appears mandatory to induce maturation of dominant-size follicles leading to ovulatory competence [38].…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, since peripherallyinjected Kp in the ewe does not cross the blood-brain barrier but nevertheless triggers the LH surge, a direct effect of Kp towards GnRH cell bodies within the rostral hypothalamus does not appear to be the primary mechanism by which the surge is initiated. To the best of our knowledge there are no data regarding these issues in mare and the very existence of a positive feed-back remains questionable [37]. Classical experiments in sheep have shown that pulsatility of GnRH governs pulsatile release of LH [56,57], a feature which appears critical for the function of the hypothalamo-pituitary-gonadal axis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol concentrations are very low, much lower than values we have published in the past, using our H3-E2-RIA (Behrens et al 1993, Hoppen 1995. However, the above data agree with recent reports from the literature (Gastal et al 1999, Ginther et al 2005, Ginther et al 2007. One possible explanation for these discrepancies may be the higher cross reactivities of the H3-E2-RIA with estrone, equilin, and equilenin.…”
Section: Normal Ovarian Cyclessupporting
confidence: 83%
“…Mares were randomly assigned to each of three groups (n ¼ 5 mares/group) according to which ovaries were collected during an ovulatory wave 1) once the largest growing follicle reached 22.0 mm in diameter, corresponding to the ED phase; 2) once the follicle reached 33.0 mm, corresponding to the late dominant (LD) phase and before the expected beginning of an endogenous ovulationinducing increase in circulating LH [19]; or 3) at the PO phase, 34 h after an i.v. injection of an ovulatory dose of crude equine gonadotropins (CEG; 15 mg i.v.…”
Section: Experimental Groups and Proceduresmentioning
confidence: 99%